2013
DOI: 10.1111/jpm.12087
|View full text |Cite
|
Sign up to set email alerts
|

Personal beliefs, learned resourcefulness, and adaptive functioning in depressed adults

Abstract: Research has shown that patients with depression have difficulty with performing daily tasks and meeting their own personal care needs. According to Beck's cognitive theory of depression, such deficits in adaptive functioning are affected by disturbances in specific personal beliefs that reflect the process of regulating cognitions. Rosenbaum's learned resourcefulness theory proposed that adaptive functioning is influenced by learned resourcefulness, while learned resourcefulness is associated with the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
(67 reference statements)
2
13
0
3
Order By: Relevance
“…(1996) that older people who viewed challenging situations as opportunities for personal growth had more positive experiences with relocation than those who did not. Lai (2005) also found that having a positive view of the self and the world was associated with adaptive functioning, which may be a hallmark of relocation adjustment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…(1996) that older people who viewed challenging situations as opportunities for personal growth had more positive experiences with relocation than those who did not. Lai (2005) also found that having a positive view of the self and the world was associated with adaptive functioning, which may be a hallmark of relocation adjustment.…”
Section: Discussionmentioning
confidence: 88%
“…, 2011a). Research has shown that positive cognitions are positively correlated with adaptive functioning and better adjustment (Lai, 2005; Bekhet et al. , 2011a,c).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The parallel administration of these two instruments -OASR and OABCL -provides standardized data on the elderly, and also considers the evaluation of family members or caregivers (Brigidi et al,, 2010). Other instruments have shown that failures in adaptive functioning affect mental health and quality of life in aging (Lai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…I now know what is most important in my life… Participants illustrated their positiveness (post ACEs) in their interaction and engagement with others, externalising their positive social values and beliefs. Studies confirm that learned efficacy and personal beliefs and values (such as self-worth, judgment, dependability, credibility and self-regulation) were related to personal adjustment following adverse experiences (Lai, Zauszniewski, Tang, Hou, Su and Lai, 2014;Turner, Goodin and Lokey, 2012). People who have a receptive cognitive style will be enabled to be accepting, tolerant, and non-judgmental (Tedeschi, 1999).…”
Section: Renewed Appreciation For Lifementioning
confidence: 99%